Designing Student Participation in Synchronous Writing Instruction - Lucy Macnaught; Jennifer Yates (Cranmore Publishing, 2020)
Although various e-learning technologies have been in use for decades, the rapid worldwide spread of COVID-19 has made online teaching and learning 'the new normal'. Many academic units, such as our team of Learning Advisors at Auckland University of Technology, have had to make quick decisions about the design of online learning experiences for students. This study reports on the creation of online writing workshops for postgraduate research students. In our context, research students can self-enrol in 'one-off' workshops where they typically do not know each other. As teaching staff, we also had little prior knowledge of how best to design student participation in synchronous writing activities. An initial challenge was thus to identify different means through which students can participate online, and then use these findings to inform workshop design. Our findings centre on an online participation matrix with two sets of simultaneous options: whether participants are identified or not; and whether their participation occurs as a series of discrete actions by individuals, or as simultaneous actions by multiple participants. In Blackboard Collaborate Ultra, we found that these combinations give rise to observant, anonymous, episodic, concealed, or discursive participation. We define and illustrate each of these participation types, discuss their sequencing across an entire workshop, and reflect on specific adaptations from face to face settings. These findings are of particular relevance to teachers who are exploring a variety of software features and want to make principled choices for the design of activities in online writing workshops.